Pengembangan Masyarakat melalui Penetapan dan Penegasan Batas di Desa Ledokombo Kabupaten Jember - Fikri Habibur Rohman; Julio Sukamto; Robi Mohammad Arifin; Muhammad Farhan Alfiansyah (Fakultas Dakwah IAIN Jember, 2022)
Ledokombo Village is a village which is located in Ledokombo District, Jember Regency. Ledokombo Village is a village that has 3 Krajan Hamlets, Sumber Nangka Hamlet, and Krajan Hamlet. Lodokombo Village itself has an area limit of 658.5 hectares. Lodokombo District has several villages and one of them is Ledokombo Village, and this Ledokombo Village there must be a re-emphasis on the boundary between Ledokombo Village and other villages. The emphasis here is not only oriented to village boundaries but also to Dusun boundaries, the emphasis here is also a manifestation of increasing awareness of village and hamlet boundaries for the people of Ledokombo Village. Our service is nothing but the aim of preventing conflicts between village boundaries and hamlets in Lodokombo Village. The determination and affirmation of village boundaries has an important and positive impact on the community as stated in Permendagri Number 27 of 2006. So the substance can be seen how important village boundaries are to clarify or reinforce village boundaries with one another